ВПЛИВ ВЕЛИЧИНИ ЄМНОСТІ ПОСЛІДОВНОГО РЕЗОНАНСНОГО КОНТУРУ НА ПОТУЖНІСТЬ ЕЛЕКТРОТЕХНІЧНИХ СИСТЕМ РЕЗОНАНСНОГО ТИПУ ДЛЯ МОНІТОРИНГУ ІЗОЛЯЦІЇ ВИСОКОВОЛЬТНОГО ОБЛАДНАННЯ - Супруновська, Н.І.; Вінниченко, Д.В. (Інститут електродинаміки НАН України, Київ, 2024)
It were analyzed the processes of charging the capacitive electro-technical storage (CES), which can be the electrical insulation of modern high -voltage equipment (in particular power cables) during the current monitoring of its technical condition by the value of leakage currents when applying high voltage to insulation. The transformerless electro-technical system (ETS) of a resonance type, in which resonant inductive-capacitive circuit (ICС) with a high Q -factor carried out a multiple increase in AC voltage, was used to generate such voltage. Analytical expressions were obtained for the steady-state voltage on such CES and transient currents in the ETS circuit its charging. Simulation modeling of transient processes in the circuits of such ETS during CES charging was performed using the LTSpice software package. It is shown that the dependences of the output voltage and current of the ETS on time, obtained by analytical expressions, practically coincide with the results of simulation simulations. The influence of the ratio of the load capacitance and the resonant circuit capacitance on the relative load charging time and, accordingly, on the ETS power was studied. It was found that in order to increase the power of high -voltage transformerless ETS of the specified resonance type, it is necessary to increase the ratio of the CES capacity to the ICС capacity of the resonant circuit of the ETS. This approach can be used when using ETS with resonant ICCs to create powerful electric discharge installations (EDIs) for the implementation of technologies for obtaining electro-spark micro- and nanopowders with unique operational properties. When creating powerful EDIs, it is suggested to use the value of the above-mentioned ratio at least 10. References 31, figures 5.